Sustainability Assessment of Machining Processes - Raza, Syed Waqar (2013)
A Master of Science thesis in Mechanical Engineering by Syed Waqar Raza entitled, "Sustainability Assessment of Machining Processes," submitted in December 2013. Thesis advisor is Dr. Ibrahim Mostafa Deiab. Available are both soft and hard copies of the thesis.